Results of a quantitative Delphi study investigating needs of people with Traumatic Brachial Plexus Injury - Hofmann Veronika; Maufroy Christophe; Pott Peter P.; Schneider Urs (Current Directions in Biomedical Engineering)
Traumatic Brachial Plexus Injury (TBPI) causes arm paralysis, impacting daily activities and reintegration into work. This paper presents the results of the first round of a quantitative Delphi study. The aim is to gather insights from five expert groups. The investigated user requirements primarily encompass design aspects like weight, fitting, and adjustability to accommodate adaptations. Besides increased functionality, a benefit for psychological recovery is presumed.